Second European Quality of Life Survey Subjective well-being in Europe - Watson, Dorothy; Pichler, Florian; Wallace, Claire; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
The way we feel about ourselves and assess the quality of our lives is influenced by many factors. Some of them are objective: how much we earn and what we can afford to buy, for example. But quality of life is not only determined by the standard of living we have attained. Objective conditions are certainly linked to our subjective well-being, but not in a straightforward manner. This report looks at the diverse factors that influence levels of subjective well-being. It explores the impact of demographic and socioeconomic factors, of health, social support and the quality of the societies we live in. It asks to what extent these factors can explain the variations seen in levels of subjective well-being in different countries. The study also examines whether social support and good public services can cushion the impact of difficult social and economic conditions experienced by European citizens, thus contributing to an improved quality of life.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Social surveys -- European Union countries; Quality of life -- European Union countries; European Union countries -- Social conditions; Electronic books